The Effect of Emotional Value and Perceived System Quality on Recommendation Intention on Customer Online Travel Services - Farhan Muhammad Kamil Danopa; Nita Hernita (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to identify the influence of emotional value and perceived system quality on recommendation intention in online travel services. In the competitive online travel industry, the ability to retain and increase customer loyalty relies heavily on the experience perceived by users. Emotional value, which includes positive feelings that arise during interactions with the service, as well as perceived system quality, which includes technical factors such as speed, ease of use, and platform reliability, are believed to have a significant influence on customers' intention to recommend the service to others. This study adopts a quantitative approach with a survey method of online travel service users who have interacted with the platform. Results from data analysis show that the emotional value perceived by customers has a positive and significant influence on recommendation intentions, while perceived system quality also plays an important role in strengthening this relationship. This research provides insights for online travel service managers to understand the factors that influence customer recommendation intentions and how they can be used to improve user experience and customer loyalty.